Coal as the National Energy Supplier Forward: What are Policies to be Prepared? - Hanan Nugroho (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2017)
Indonesia’s energy security is critical, coal which is expected to be the backbone of national energy supply also faces considerable challenges. To overcome this, it is necessary to formulate a policy of production control, export restrictions, as well as concerning the economy, environment and infrastructure of coal. The paper recommends that: (i) Develop depletion policies to control coal production, (ii) Implement strict discipline in granting mining permits, (iii) Reduce coal exports through export taxes, (iv) Develop more appropriate DMO (domestic market obligation) policies (v) Utilizing coal as energy to drive activities and provide added value to the domestic economy, (vi) Increasing the application of clean coal technology, and (vii) Accelerating the development of transportation, storage, and utilization of coal to serve the needs of domestic demand